(3QSGFd ehLRI aj JYQja GdWH heSGFd eJYdbI Hgs - (3TeS GdOjf eJWHH cjdGfj (B( (3GdLjdGfj (B)s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHg KbJi GdaUd GdChd ai Cf GdWH UfGYI hEfgG CaVd GdUfGjY bO jfbSe GdTF GdfGaY Ydi gPg GdbSeI ajbGd fGaY VQhQi hfGaY ZjQ VQhQi s
(3BNQgG (B:s
(3BNQ GdehLhO efgG (B: (3Ef GdTF GdPi jMJGL Edi JSNjf jROGO hGdTF GdPi jMJGL Edi GdJHQjO Ke jSNf aEfg bO Yed HNdGa eG jSjQ HgG GdWHjYI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1/3381) s
Keywords: (3GdWHs